2010
DOI: 10.1097/mat.0b013e3181d0ea15
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Swirling Flow on Platelet Adhesion to the Surface of a Sudden Tubular Expansion Tube: Its Potential Application in End-to-End Arterial Anastomosis

Abstract: The size mismatch in an end-to-end vascular anastomosis between the host vessel and the graft may cause flow disturbance and possibly result in thrombosis. To test the hypothesis that intentionally induced swirling flow in an end-to-end anastomosis could suppress flow disturbance, impeding thrombus formation by affecting platelets adhesion, a comparative study was designed to investigate the effect of swirling flow on the adhesion and activation of platelets in a glass sudden tubular expansion tube coated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…We tested this hypothesis experimentally by studying the effect of swirling flow on platelet adhesion and activation in a straight glass tube and a sudden tubular expansion tube, which were used to mimic a small-caliber graft and an end-to-end anastomosis [12,13]. The experimental study demonstrated that swirling flow could indeed significantly reduce the number of adherent platelets in both the straight glass tube and the sudden expansion tube.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…We tested this hypothesis experimentally by studying the effect of swirling flow on platelet adhesion and activation in a straight glass tube and a sudden tubular expansion tube, which were used to mimic a small-caliber graft and an end-to-end anastomosis [12,13]. The experimental study demonstrated that swirling flow could indeed significantly reduce the number of adherent platelets in both the straight glass tube and the sudden expansion tube.…”
Section: Introductionmentioning
confidence: 90%
“…The present numerical simulation is a supplementary study to our previous experimental study [12,13]. Two groups of numerical models were created based on our previous study: the straight tube group and the sudden tubular expansion tube group (Fig.…”
Section: Geometric Modelmentioning
confidence: 99%
See 3 more Smart Citations